A review of mites of the subfamily Speleognathinae (Acariformes: Ereynetidae) parasitizing respiratory tracts of birds in the Afrotropical region - Skoracki, Maciej; Schmidt, Karl-Heinz; Marciniak, Natalia; Marciniak, Martyna (Zootaxa, 2018)
Nasal mites of the subfamily Speleognathinae associated with birds in the Afrotropical region are reviewed. The total of 37 species belonging to15 genera has been recorded so far in this region. All recorded species and genera are provided with improved diagnoses, data on their host associations and distribution are summarized, and a key to all species is constructed.